Si nanowires produced by very high frequency plasma enhanced chemical vapor deposition via VLS mechanism - Yussof Wahab,; Habib Hamidinezhad,; Zulkafli Othaman, (Universiti Kebangsaan Malaysia, 2013)
Silicon nanowires (SiNWs) with diameter of about a few nanometers and length of 3 μm on silicon wafers were synthesized by very high frequency plasma enhanced chemical vapor deposition. Scanning electron microscopy (SEM) observations showed that the silicon nanowires were grown randomly and energy-dispersive X-ray spectroscopy analysis indicates that the nanowires have the composition of Si, Au and O elements. The SiNWs were characterized by high resolution transmission electron microscopy (HRTEM) and Raman spectroscopy. SEM micrographs displayed SiNWs that are needle-like with a diameter ranged from 30 nm at the top to 100 nm at the bottom of the wire and have length a few of micrometers. In addition, HRTEM showed that SiNWs consist of crystalline silicon core and amorphous silica layer.